THE DISTRIBUTION AND BEHAVIOUR OF RE AND OS AMONGST MANTLE MINERALS AND THE CONSEQUENCES OF METASOMATISM AND MELTING ON MANTLE LITHOLOGIES - Burton, Kevin W.; Schiano, Pierre; Birck, Jean-Louis; Allègre, Claude J; Rehkämper, Mark; Halliday, Alex N. (Ofioliti, 1999)
The fractionation of Re and Os during basalt genesis is one of the key processes governing the present-day distribution of these elements between the earth’s crust and mantle. However, the cause of this fractionation remains poorly understood, in a large part because there is little information on the distribution and behaviour of Re and Os in mantle minerals. This study presents rhenium-osmium (Re-Os) isotope and elemental abundances for primary mantle minerals, metasomatic phases, and a range of mantle rock types from xenoliths in recent voclanics in northern Tanzania. These results provide quantitative constraints on the distribution of Re and Os amongst mantle minerals, enable an assessment of the effects of metasomatism, and an understanding of the behaviour of Re and Os during melting and the consequences for the chemistry of the mantle residue.Re and Os abundances for sulphide and coexisiting silicates in garnet lherzolites from Lashaine confirm that sulphide dominates the Os budget (e.g. Hart and Ravizza, 1996), but also show that Re is almost exclusively sited in silicate phases. Silicate minerals from two different samples yield 187Re-188Os ages of 32±12 and 15±8 Myr, respectively. Comparison with 147Sm-143Nd, 87Rb-87Sr, and 232Th-208Pb ages for the same silicate minerals suggests differential closure between these isotope systems, and a closure temperature of about 700°C for the Re-Os system. However, sulphide inclusions preserve significantly less radiogenic Os isotope compositions, suggesting that they have been shielded from reaction or diffusion by their silicate hosts. Diffusion rates in sulphides are likely to be rapid at mantle temperatures (e.g. Birchenall, 1974), however, for sulphide inclusions diffusion through the silicate host is likely to be impaired by the high partition coefficient between sulphide and silicate pahses (Hofmann and Hart, 1978). The Os isotope composition of the sulphide (187Os/188Os = 0.10432±13) suggests a minimum age of 3.4 Gyr, indicating that the subcontinental lithospheric mantle in Tanzania, has a similar longevity to the Kaapvaal craton (Pearson et al., 1995).Whole-rock samples from Labait, Olmani and Lashaine generally have Os isotope compositions that are less radiogenic than estimates for the present-day upper mantle, suggesting Re loss occurred some time ago. Samples containing metasomatic phlogopite possess high Re concentrations and Re/Os ratios, but that they also possess relatively unradiogenic Os isotope compositions suggests that the metasomatism occurred relatively recently, consistent with data for metasomatic minerals. Some dunites possess both high Re/Os ratios and radiogenic Os isotope compositions. These samples differ from those affected by modal metasomatism in having exceptionally low Os concentrations (containing as little as 10 ppt Os). These rocks are extremely refractory and are considered to have experienced extensive melt loss (e.g. Rudnick et al, 1992). The Re-Os data are consistent with complete removal of sulphide during melting, leaving a radiogenic silicate residue with an extremely low Os concentration. These results suggest that at least some of the radiogenic Os component in the mantle, sampled by oceanic basalts, may arise from mantle processes themselves (prior melting or metasomatism) rather than from recycling (e.g. Hauri and Hart, 1993), or contribution from the lower mantle or core (Widom and Shirey, 1996).